Social support of veterans of the Russian-Ukrainian war and their families during the war and post-war period - Slozanska, Hanna; Horishna, Nadiia; Bybyk, Daria; Krynytska , Iryna (Social work and education, 2023)
The increase in the number of veterans/veterans in connection with the full-scale invasion of Russia on the territory of Ukraine has exacerbated the issue of developing effective mechanisms for their social support at the state level. The article offers its own understanding of the content of social support; the results of the study of the available domestic and foreign experience in the organization of social support for veterans in the activities of primary state and communal institutions are highlighted; the work prospects of state and communal institutions of relevant ministries (the Ministry of Defense, the Ministry of Veterans Affairs and the Ministry of Social Policy) regarding the implementation of social support for veterans of the Russian-Ukrainian war and their families were developed and highlighted. It is noted that social support is a set of activities, programs and services provided by local authorities, public organizations and other institutions or organizations with the aim of facilitating the process of reintegration and ensuring a dignified life for veterans/veterans and their family members. It was determined that the primary institutions for the organization and implementation of social support for the specified population category are three institutions: territorial recruitment and social support centers of the Ministry of Defense, territorial departments of the Ministry of Veterans Affairs, Centers for the provision of social services/Centers of social services of the Ministry of Social Policy, which are obliged it is necessary to clearly divide powers and take responsibility for the implementation of social support for veterans/veterans and their family members.